The role of oxidative stress in the development of knee osteoarthritis: A comprehensive research review - Liu, Lin; Luo, Pan; Yang, Mingyi; Wang, Jiachen; Hou, Weikun; Xu, Peng (Frontiers in Molecular Biosciences, 2022)
Knee osteoarthritis (KOA) is one of the most common degenerative diseases, and its core feature is the degeneration and damage of articular cartilage. The cartilage degeneration of KOA is due to the destruction of dynamic balance caused by the activation of chondrocytes by various factors, with oxidative stress playing an important role in the pathogenesis of KOA. The overproduction of reactive oxygen species (ROS) is a result of oxidative stress, which is caused by a redox process that goes awry in the inherent antioxidant defence system of the human body. Superoxide dismutase (SOD) inside and outside chondrocytes plays a key role in regulating ROS in cartilage. Additionally, synovitis is a key factor in the development of KOA. In an inflammatory environment, hypoxia in synovial cells leads to mitochondrial damage, which leads to an increase in ROS levels, which further aggravates synovitis. In addition, oxidative stress significantly accelerates the telomere shortening and ageing of chondrocytes, while ageing promotes the development of KOA, damages the regulation of redox of mitochondria in cartilage, and stimulates ROS production to further aggravate KOA. At present, there are many drugs to regulate the level of ROS, but these drugs still need to be developed and verified in animal models of KOA. We discuss mainly how oxidative stress plays a part in the development of KOA. Although the current research has achieved some results, more research is needed.